Detoxifying Enzymatic Activity and Insecticide-Resistance Gene Expression in Field Populations of Pink Bollworm, (Pectinophora gossypiella (Saund.)) - Rabab Desouky Alam; Amgad Sobeiha; Abdel-Aziz Khdir; Naima Alsenosy (Arab Universities Journal of Agricultural Sciences, 2021)
A study was conducted to assess two enzyme detoxifying activities and insecticide-resistance gene expression quantitation using real-time (PCR). Four populations of pink bollworms were compared with the baseline laboratory strain. Field populations showed higher levels of enzymatic activity, glutathione-S-transferase and β–esterases, than those of the laboratory strain. The amplification curves scored a cycle threshold (Ct) value of 25 for the ribosomal protein subunit7 (rps7). For the BtR gene, the Ct values of analyzed biological groups ranged from 20 for the laboratory strain to 24 for the Fayoum group. For Cad1, the Ct values ranged from 19 for laboratory strain to 23 for Fayoum and Qalubia populations. Therefore, the present work introduces a method for the challenge of monitoring resistance to Bt toxins in crops which requires, according to the IPM (Integrated Pest Management) program, a wise insecticide application.